Research on the Texture Design of Automobile Leather Seats based on Perceptual Engineering and Fuzzy Analytic Hierarchy Process - Qinglan WAN; Yueqin WU (Pige Kexue Yu Gongcheng)
In order to gain an in-depth understanding of consumers' perceptual needs for automobile leather seats, consumers aged 25-44 were selected for experimental research. Firstly, four pairs of perceptual words were selected through research, focus group and other methods: business/sports, high-end/economy, traditional/modern, and complex/simple. With the help of morphological analysis, the texture elements of automobile leather seats were deconstructed, and five types of texture forms were obtained: color, luster, texture, pattern and texture. Secondly, the fuzzy analytic hierarchy process was used to construct the hierarchical index system and the fuzzy function evaluation matrix to quantify the perceptual needs of consumers. The correlation between the user's perceptual intention and the texture design elements was further analyzed, and the combination of automotive leather seat texture design elements that met the user's perceptual needs was proposed. In addition, the texture elements representing special perceptual intentions were applied to the design of automotive leather seats, in order to provide a reference for the color, material, and surface treatment (CMF) of automotive seats.